Sčítání a odčítání výrazů

1)        Upravte:

\displaystyle a)\quad 3x+2y+7x=

\displaystyle b)\quad 5r+4s-r+2s=

\displaystyle c)\quad 2m+9n-3n-m=

\displaystyle d)\quad 7a+3b-7a+3b=

\displaystyle e)\quad 6p+10q-5p-q=

\displaystyle f)\quad ax+2ay+8ax-2ay=

\displaystyle g)\quad 4a+2b+c-3a+3b+c=

\displaystyle h)\quad 5xy+2x+11y-2x-8y=

 

2)        Upravte:

\displaystyle a)\quad 3x-5+4x+9=

\displaystyle b)\quad 4t+2-t-7=

\displaystyle c)\quad 2m+9n-3n-m=

\displaystyle d)\quad 7a+3b-7a+3b=

\displaystyle e)\quad 6p+10q-5p-q=

\displaystyle f)\quad ax+2ay+8ax-2ay=

\displaystyle g)\quad 4a+2b+c-3a+3b+c=

\displaystyle h)\quad 5xy+2x+11y-2x-8y=

 

3)        Upravte:

\displaystyle a)\quad 2+4{{a}^{2}}-3{{a}^{2}}-1+3a+{{a}^{3}}-2a=

\displaystyle b)\quad 11-5t-{{t}^{2}}+4t-8+3{{t}^{2}}=

\displaystyle c)\quad 3u-8u+{{u}^{4}}-2{{u}^{2}}-4{{u}^{3}}+3{{u}^{2}}+{{u}^{3}}=

\displaystyle d)\quad 4{{x}^{2}}-2{{x}^{4}}+{{x}^{2}}-5{{x}^{3}}-{{x}^{2}}+3{{x}^{4}}+5{{x}^{3}}=

 

4)        Zjednodušte:

\displaystyle a)\quad \left( -6x \right)+2x+\left( -3x \right)+\left( +10x \right)=

\displaystyle b)\quad \left( +a \right)+\left( -7a \right)+\left( -4a \right)+\left( +5a \right)+\left( +3a \right)=

\displaystyle c)\quad \left( -4{{a}^{2}}b \right)+\left( -2ab \right)+\left( -{{a}^{2}}b \right)+\left( +6{{a}^{2}}b \right)+9ab=

\displaystyle d)\quad \left( +xy \right)+\left( -5xy \right)+\left( -3xy \right)+\left( +9xy \right)+\left( -2xy \right)=

 

5)        Zjednodušte:

\displaystyle a)\quad 2a-\left( a-b+c \right)=

\displaystyle b)\quad 5z-\left( 3z-4 \right)-7=

\displaystyle c)\quad \left( a-3 \right)-\left( 3a-2 \right)=

\displaystyle d)\quad \left( 6x-y+1 \right)-\left( 2x-3y-1 \right)=

\displaystyle e)\quad \left( 5y-3 \right)-\left( 3y-2 \right)=

\displaystyle f)\quad \left( 4x-2y+1 \right)-\left( -2y-3x-5 \right)=

 

6)        Zjednodušte:

\displaystyle a)\quad \left( 5b+4 \right)-\left( 2b+3 \right)=

\displaystyle b)\quad \left( 3x-7 \right)-\left( 9x+1 \right)=

\displaystyle c)\quad \left( 26y-9 \right)-\left( -7y-2 \right)=

\displaystyle d)\quad \left( -8y+3 \right)-\left( 15y-4 \right)=

\displaystyle e)\quad \left( -3{{a}^{2}}-b \right)-\left( 2{{a}^{2}}-b \right)=

\displaystyle f)\quad -\left( b-2a+4 \right)-\left( 2b-a+2 \right)=

\displaystyle g)\quad -\left( 3x-y-c \right)-\left( -2x+y+2c \right)=

\displaystyle h)\quad -\left( -a-2b+3 \right)-\left( 3a+2b+4 \right)=

 

7)        Zjednodušte:

\displaystyle a)\quad \left( 2a+3b-4 \right)+\left( 5a-6b+1 \right)+\left( -3a-6b-6 \right)=

\displaystyle b)\quad \left( k-3 \right)+\left( 5k+9 \right)+\left( 7k+1 \right)=

\displaystyle c)\quad \left( 7m+n-8 \right)+\left( 4m-5n+5 \right)+\left( 7m-2n-2 \right)=

\displaystyle d)\quad \left( -5p-6u+3 \right)+\left( 7p+3u \right)+\left( 4u-9 \right)=

\displaystyle e)\quad \left( s+h-1 \right)+\left( -2h+6s+5 \right)+\left( h-6 \right)=

\displaystyle f)\quad \left( 6t-5w+9 \right)+\left( 5w-11t-7 \right)=

\displaystyle g)\quad \left( 7o-9p+11 \right)+\left( 7o+6p-12 \right)+\left( 2p-2o+2 \right)=

\displaystyle h)\quad \left( 4y-9k+h-9 \right)+\left( h-k+4y \right)+\left( 6y-5k+8h-5 \right)=

 

8)        Zjednodušte:

\displaystyle a)\quad \left( 6q-2a+9 \right)+\left( 7q-3a-8 \right)+\left( 4q-4a+5 \right)=

\displaystyle b)\quad \left( 11o+18p \right)+\left( 31o-6p \right)=

\displaystyle c)\quad \left( 3u+9j-5f+6 \right)+\left( 11u-5j+6f-9 \right)+\left( 6u+4j-9f+11 \right)=

\displaystyle d)\quad \left( 9p-6d+3 \right)+\left( 5d+3v-9 \right)+\left( 5p+6v-11 \right)=

\displaystyle e)\quad \left( 8r-6z+4 \right)+\left( 6w+7r+3 \right)+\left( 5w-z \right)=

\displaystyle f)\quad \left( 8o-9p+k-6 \right)+\left( 7o-p+9k-1 \right)+\left( 5o-3p+9k \right)+\left( 2p-o+6k-9 \right)=

\displaystyle g)\quad \left( 4u-5v-6d-5 \right)+\left( -6u+9v-8d+8 \right)+\left( -8u+6v-6d-15 \right)=

\displaystyle h)\quad \left( 11t-2s+2u-2 \right)+\left( -8t+5s+6u \right)+\left( 9t-10s+9u-14 \right)=

 

9)        Zjednodušte:

\displaystyle a)\quad \left( 14a-5b+3d+6 \right)+\left( 5a-9b+3c \right)+\left( -c+a-2b-9k \right)=

\displaystyle b)\quad \left( 9p+5m+3 \right)+\left( 6p-9m+9 \right)+\left( 10p-13m-15 \right)+\left( -p+m-2 \right)=

\displaystyle c)\quad \left( 2a+3b-4 \right)-\left( 5a-6b+1 \right)-\left( -3a-6b-6 \right)=

\displaystyle d)\quad -\left( k-3 \right)-\left( 5k+9 \right)-\left( 7k+1 \right)=

\displaystyle e)\quad \left( 7m+n-8 \right)-\left( 4m-5n+5 \right)-\left( 7m-2n-2 \right)=

\displaystyle f)\quad \left( -5p-6u+3 \right)-\left( 7p+3u \right)-\left( 4u-9 \right)=

\displaystyle g)\quad -\left( s+h-1 \right)-\left( -2h+6s+5 \right)-\left( h-6 \right)=

\displaystyle h)\quad -\left( 6t-5w+9 \right)-\left( 5w-11t-7 \right)=

 

10)        Zjednodušte:

\displaystyle a)\quad -\left( 7o-9p+11 \right)-\left( 7o+6p-12 \right)-\left( 2p-2o+2 \right)=

\displaystyle b)\quad -\left( 4y-9k+h-9 \right)-\left( h-k+4y \right)-\left( 6y-5k+8h-5 \right)=

\displaystyle c)\quad -\left( 6q-2a+9 \right)-\left( 7q-3a-8 \right)-\left( 4q-4a+5 \right)=

\displaystyle d)\quad \left( 11o+18p \right)-\left( 31o-6p \right)=

\displaystyle e)\quad \left( 3u+9j-5f+6 \right)-\left( 11u-5j+6f-9 \right)-\left( 6u+4j-9f+11 \right)=

\displaystyle f)\quad -\left( 9p-6d+3 \right)-\left( 5d+3v-9 \right)-\left( 5p+6v-11 \right)=

 

11)        Zjednodušte:

\displaystyle a)\quad \left( 8r-6z+4 \right)-\left( 6w+7r+3 \right)-\left( 5w-z \right)=

\displaystyle b)\quad \left( 8o-9p+k-6 \right)-\left( 7o-p+9k-1 \right)-\left( 5o-3p+9k \right)-\left( 2p-o+6k-9 \right)=

\displaystyle c)\quad -\left( 4u-5v-6d-5 \right)-\left( -6u+9v-8d+8 \right)-\left( -8u+6v-6d-15 \right)=

\displaystyle d)\quad \left( 11t-2s+2u-2 \right)-\left( -8t+5s+6u \right)-\left( 9t-10s+9u-14 \right)=

\displaystyle e)\quad -\left( 14a-5b+3d+6 \right)-\left( 5a-9b+3c \right)-\left( -c+a-2b-9k \right)=

\displaystyle f)\quad -\left( 9p+5m+3 \right)-\left( 6p-9m+9 \right)-\left( 10p-13m-15 \right)-\left( -p+m-2 \right)=

 

12)        Zjednodušte:

\displaystyle a)\quad 4-\left( x-1 \right)+\left( x+2 \right)-5x-9+\left( 3x-4 \right)=

\displaystyle b)\quad 7m-\left( 2-2m \right)-\left( 3m+5 \right)-8+\left( 6+3m \right)=

\displaystyle c)\quad 4a-11-\left( 5a+4 \right)-\left( -3-4a \right)+a=

\displaystyle d)\quad y-\left( 2y-5 \right)+\left( 6-y \right)-\left( -9-2y \right)-y=

\displaystyle e)\quad -3-\left( -2-7t \right)-\left( -t+6 \right)+\left( 3-5t \right)-10t=